The impact of automation system on job satisfaction and performance level of cash division employees. - Justiniani, Jo Elizabeth E. (1999.)
This study sought to find out whether automation has a significant effect on job satisfaction and performance of employees. This was conducted as a follow-up study on previous researches on the relationship between the same variables but considered automation as a factor in work setting., Fifteen (15) cash division employees of three academic state universities and colleges were purposively chosen as respondents for this study. Seven (7) of the respondents were from the University of the Philippines in the Visayas (UPV), five (5) from the West Visayas State University (WVSU)< and three (3) from Western Visayas College of Science and Technology (WVCST). Data was gathered by the use of a standard scale on job satisfaction by Paul Spector of the Department of Psychology in the University of South Florida. A survey questionnaire was also used to get other relevant data. The employees' performance appraisal ratings both a year prior and after automation was implemented were obtained from each institution's Human Resources and Development Office (HRDO). The respondents classified all job functions to be either automated (A) or non-automated (NA). The results however showed inconsistency in their classification. Some same office functions were identified as automated while others non-automated. Results also showed that the respondents perceived an increase in their efficiency (mean = 4.2), productivity (mean =3.9), quantity of work (60), and job satisfaction (86.67) with the presence of automation in their respective work places. Hence, an increase in the respondents' over-all job performance can be attributed to the adaptation of this new system. T-test also revealed a significant difference between performances before and during automation 9Xbefore = 67.71 (Xduring=81). The study also revealed a weak positive correlation between the same varibles (r = .214). It implied that for every variation in performance only 4 of that variation could be attributed to the relationship between job satisfaction and performance. Therefore, automation has no relevance in the perceived relationship between the two variables.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Automation System